Positive deviance control-case life history: a method to develop grounded hypotheses about successful long-term avoidance of infection - Sandoval Milagros; Mateu-Gelabert Pedro; Friedman Samuel R; Hagan Holly; Jarlais Don (BMC, 2008)
Abstract Background Prevalence rates for long-term injection drug users in some localities surpass 60% for HIV and 80% for HCV. We describe methods for developing grounded hypotheses about how some injectors avoid infection with either virus. Methods Subjects: 25 drug injectors who have injected drugs 8 - 15 years in New York City. 17 remain without antibody to either HIV or HCV; 3 are double-positives; and 5 are positive for HCV but not HIV. "Staying Safe" methodology compares serostatus groups using detailed biographical timelines and narratives; and information about how subjects maintain access to physical resources and social support; their strategies and tactics to remain safe; how they handle problems of addiction and demands by drug dealers and other drug users; and how their behaviors and strategies do or do not become socially-embedded practices. Grounded theory and life-history analysis techniques compare and contrast doubly-uninfected with those infected with both viruses or only with HCV. Results Themes and initial hypotheses emerging from analyses included two master hypotheses that, if confirmed, should help shape preventive interventions: 1) Staying uninfected is not simply a question of social structure or social position. It involves agency by drug injectors, including sustained hard work and adaptation to changing circumstances. 2) Multiple intentionalities contribute to remaining uninfected. These conscious goals include balancing one's need for drugs and one's income; developing ways to avoid drug withdrawal sickness; avoiding situations where other drug users importune you to share drugs; and avoiding HIV (and perhaps HCV) infection. Thus, focusing on a single goal in prevention might be sub-optimal. Other hypotheses specify mechanisms of enacting these intentionalities. One example is finding ways to avoid extreme social ostracism. Conclusion We have identified strategies and tactics that some doubly-uninfected IDUs have developed to stay safe. Staying Safe methodology develops grounded hypotheses. These can be tested through cohort studies of incidence and prevention trials of hypothesis-based programs to help drug injectors make their injection and sexual careers safer for themselves and others. This positive deviance control-case life history method might be used to study avoiding other infections like genital herpes among sex workers.